Dye-sensitized InGaN nanowire arrays for efficient hydrogen production under visible light irradiation. (29th June 2015) - Kibria, M G; Chowdhury, F A; Trudeau, M L; Guo, H; Mi, Z
Abstract: Solar water splitting is a key sustainable energy technology for clean, storable and renewable source of energy in the future. Here we report that Merocyanine-540 dye-sensitized and Rh nanoparticle–decorated molecular beam epitaxially grown In0.25 Ga0.75 N nanowire arrays have produced hydrogen from ethylenediaminetetraacetic acid (EDTA) and acetonitrile mixture solution under green, yellow and orange solar spectra (up to 610 nm) for the first time. An apparent quantum efficiency of 0.3% is demonstrated for wavelengths 525–600 nm, providing a viable approach to harness deep-visible and near-infrared solar energy for efficient and stable water splitting.